Implementasi etika bisnis untuk meningkatkan profesionalisme akunting - Qamar, Syam Sawal; Ramadhan, Yanuar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Aspects of the development of individual life can not be separated from the rules and morals. Basically the attitude of human behavior is based on positive moral values. When the development of the world of accountants is experiencing a moral crisis due to the rapid pace of competitors to realize what they want in the form of demands for professionalism and large profits, this will override the value of honesty and truth. The purpose of this study is to improve the morality aspect for accounting who has a role in developing business in the accounting field. This research method uses qualitative-descriptive methods to collect data through the main informant owner Andalus City Cirebon, supporting informants 3 employees. Observation data collection techniques, interviews, Based on the results of the study suggest that there is a main role of an expert in the accounting profession in developing services in the financial sector based on personality aspects based on the values of honesty, exemplary, and increasing scientific and technological insight, thus helping accountants to increase their potential as well as increasing the value of thoroughness in acting, being able to express the right honesty in making wise decisions because accounting has more potential for service development, as an effort to achieve the target size of challenges at the national and international level.